Media guide of Sri Lanka - Wickremaratne, Dharman; Sri Lanka Environmental Journalists Forum (Nugegoda : Sri Lanka Environmental Journalists Forum, 2000)
Directory that lists about 250 names and addresses of media from all over Sri Lanka.
Page 240 is left blank for notes.
Includes index.
Keywords: Mass media -- Sri Lanka